Impact of Gut Microbiota on Immune System Regulation: A Narrative Review - Tashbolotovich, Turdubaev Kursanbek; Alhiti, Hazim Abdul Rahman; Khaled, Zaid; Albasri, Ridha Jawad Kadhim; Sabah, Ahmad; Rakhima, Azhimamatova (Trends in Immunotherapy, 2025)
The microbiota plays an essential role in the regulation of the natural immune system, influencing both innate and adaptive immunological responses. This review extracted information from available observational studies that explore the intricate cooperation between gut microbiota and immune system regulation across various health conditions, including Crohn’s disease, respiratory infections, autoimmune diseases, cancer, metabolic disorders, and infectious diseases. Key findings highlight how dysbiosis, a rotation in the microbiome composition or microbial imbalance, contributes to disease pathogenesis and immune dysregulation, while specific microbial taxa and their metabolites can serve as potential biomarkers and therapeutic targets. By analyzing these studies, the paper aims to provide a comprehensive understanding of the gut microbiota’s impact on immune function and its potential implications for disease prevention and management. In conclusion, this review comprehensively elucidates the complex relationship between gut flora and immune system regulation across various health conditions. The synthesized findings underscore the profound impact of microbiota composition on immune responses, from influencing disease susceptibility and severity to potential therapeutic interventions. Key insights include the identification of microbiota-based biomarkers for predicting treatment outcomes and disease risks, highlighting the potential for personalized medicine approaches. However, the few available observational studies, such as study design variability and the complex nature of microbiota dynamics, necessitate further mechanistic research to validate causal relationships and optimize clinical applications. Moving forward, integrating microbiota-targeted therapies and dietary interventions tailored to individual microbial profiles holds promise for mitigating immune dysregulation and improving overall health outcomes.